Identification of Filovirus Entry Inhibitors from Marine Fungus-Derived Indole Alkaloids - Leah Liu Wang; Javier Seravalli; Brett Eaton; Yi Liu; Michael R. Holbrook; Wen-Jian Lan; Shi-Hua Xiang (Marine Drugs)
Filoviruses, mainly consisting of the two genera of Ebolavirus and Marburgvirus, are enveloped negative-strand RNA viruses that can infect humans to cause severe hemorrhagic fevers and outbreaks with high mortality rates. However, we still do not have effective medicines for treating these diseases. To search for effective drugs, we have identified three marine indole alkaloids that exhibit potent activities against filovirus infection. Thus, it is suggested that marine indole alkaloids can be a valuable compound source for filovirus drug screening and development. Since marine indole alkaloids comprise a large diverse group of secondary metabolites, their biological properties would be helpful for pharmaceutical drug development to treat various filovirus infections.